Public Information Disclosure in Village Governance - Brain Fransisco Supit; Elvis Lumingkewas; Ressy Mewengkang; Stenlie Rattu; Yunita Sulistyosari (Technium Social Sciences Journal, 2024)
One of the objectives of public information disclosure, in accordance with Law No. 14 of 2008, is to realize transparent, effective, efficient, and accountable state administration. The purpose of this research is to describe the implementation of public information disclosure in village governance. The research locus is Tonsewer Village, West Tompaso District, Minahasa. The research method used is descriptive qualitative, with data collection techniques including observation, interviews, and documentation. The results indicate that Tonsewer Village has the potential to become a role model for other villages in implementing good governance and e-governance, particularly in digital public information disclosure in Minahasa. However, there are several challenges, such as the lack of public understanding of the importance of information disclosure, limited technological infrastructure, insufficient human resource capacity within the village government, and low public participation in accessing public information. Although the village already has a website containing public information, it is not yet optimal and needs further improvement. This study concludes that it is necessary to enhance the capacity of village officials, develop technological infrastructure, and improve community digital literacy to enhance public information disclosure in Tonsewer Village.